2015
DOI: 10.1074/jbc.m115.645358
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension-causing Mutations in Cullin3 Protein Impair RhoA Protein Ubiquitination and Augment the Association with Substrate Adaptors

Abstract: Background: Cullin3 ubiquitin ligase regulates protein turnover by promoting the ubiquitination of substrates. Results: Ubiquitination of RhoA is impaired by mutations in Cullin3. Conclusion: Disease-causing Cullin3 mutations impair the turnover of RhoA protein and may sequester substrates adaptors. Significance: Mutations in Cullin3 cause reduced ubiquitination and elevation of RhoA levels, which may enhance RhoA and Rho kinase signaling in a variety of cell types and could potentially contribute to hypertens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
71
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 55 publications
(77 citation statements)
references
References 46 publications
6
71
0
Order By: Relevance
“…We previously proposed that CUL3-Δ9 is an overactive form of CUL3 that inappropriately degrades KLHL3 (28). The Sigmund group reported that WT CUL3/CUL3-Δ9 heterodimers are less stable than CUL3 WT/WT homodimers, and that CUL3-Δ9 may also sequester adapters (29). Finally, the Kurz group confirmed our finding with respect to inappropriate degradation of KLHL3 but also reported that CUL3-Δ9 displays autoubiquitination, leading to its own proteasomal degradation (30).…”
Section: CLsupporting
confidence: 77%
See 3 more Smart Citations
“…We previously proposed that CUL3-Δ9 is an overactive form of CUL3 that inappropriately degrades KLHL3 (28). The Sigmund group reported that WT CUL3/CUL3-Δ9 heterodimers are less stable than CUL3 WT/WT homodimers, and that CUL3-Δ9 may also sequester adapters (29). Finally, the Kurz group confirmed our finding with respect to inappropriate degradation of KLHL3 but also reported that CUL3-Δ9 displays autoubiquitination, leading to its own proteasomal degradation (30).…”
Section: CLsupporting
confidence: 77%
“…The mechanism by which CUL3-Δ9 leads to FHHt is controversial, but this is primarily related to the fact that most studies have been performed in vitro (28)(29)(30)34). A constitutive deletion of exon 9 in mice suggested that FHHt is due to haploinsufficiency resulting from degradation of CUL3-Δ9 following autoubiquitination (30).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This results in an in-frame deletion of 57 amino acids internal to CUL3. Evidence that the mutant protein (termed CUL3Δ9) has dominant-negative activity includes that (a) CUL3Δ9 supports impaired ubiquitin ligase activity toward normal substrates, (b) CUL3Δ9 exhibits enhanced binding to substrate adaptors and promotes their degradation, and (c) CUL3Δ9 may form inhibitory and unstable heterodimers with wildtype CUL3 (CUL3WT) (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%